Closed-Incision Negative-Pressure Therapy in Obese Patients Undergoing Cesarean Delivery: A Randomized Controlled Trial - Gunatilake, Ravindu P.; Swamy, Geeta K.; Brancazio, Leo R.; Smrtka, Michael P.; Thompson, Jennifer L.; Gilner, Jennifer B.; Gray, Beverly A.; Heine, Robert Phillips (American Journal of Perinatology Reports, 2017)
Background Postcesarean wound morbidity is a costly complication of cesarean delivery for which preventative strategies remain understudied.Objective We compared surgical site occurrences (SSOs) in cesarean patients receiving closed-incision negative-pressure therapy (ciNPT) or standard-of-care (SOC) dressing.Study Design A single-center randomized controlled trial compared ciNPT (5–7 days) to SOC dressing (1–2 days) in obese women (body mass index [BMI] ≥ 35), undergoing cesarean delivery between 2012 and 2014. Participants were randomized 1:1 and monitored 42 ± 10 days postoperatively. The primary outcome SSOs included unanticipated local inflammation, wound infection, seroma, hematoma, dehiscence, and need for surgical or antibiotic intervention.Results Of the 92 randomized patients, 82 completed the study. ciNPT and SOC groups had similar baseline characteristics. Mean BMI was 46.5 ± 6.5 and no treatment-related serious adverse events. Compared with SOC, the ciNPT group had fewer SSOs (7/43 [16.3%] vs. 2/39 [5.1%], respectively; p = 0.16); significantly fewer participants with less incisional pain both at rest (39/46 [84.8%] vs. 20/46 [43.5%]; p < 0.001) and with incisional pressure (42/46 [91.3%] vs. 25/46 [54.3%]; p < 0.001); and a 30% decrease in total opioid use (79.1 vs. 55.9 mg morphine equivalents, p = 0.036).Conclusion A trend in SSO reduction and a statistically significant reduction in postoperative pain and narcotic use was observed in women using ciNPT.
Keywords: obesity; cesarean; negative pressure wound therapy; wound infection